Hippocampal dysmetabolism contributes to cognitive loss in autoimmune encephalitis and focal temporal epilepsy - Olga Taraschenko; Lakshman Arcot Jayagopal; Audrina Mullane; Kyle Greenman; Matthew White; Hesham Ghonim; Shelley Lee; Rana Khalil Zabad; Tracy Jasinski; Mariano Uberti (Frontiers in Neurology)
IntroductionAutoimmune encephalitis (AE) is associated with severe cognitive disability. Brain metabolic dysfunction has been linked to encephalopathy in neurodegenerative disorders; however, its role in the development of cognitive loss in AE has not been studied. We hypothesized that cognitively impaired patients with AE will demonstrate altered brain metabolism and immune activation, and these measures will correlate with cognitive scores.MethodsThe hippocampal and cortical metabolites related to neuronal integrity, oxidative metabolism, and glial activation were assessed using single-voxel proton magnetic resonance spectroscopy (1H-MRS) in patients with AE, non-lesional temporal lobe epilepsy (TLE) and control subjects. Metabolite levels were correlated with neuropsychological test scores.ResultsWe recruited patients with post-acute AE (n = 12), non-lesional TLE (n = 12), and control subjects (n = 11). Subjective cognitive complaints were reported by 83.3% of AE and all TLE patients. AE patients had fewer seizures and used fewer anti-seizure medications than TLE patients (p = 0.04, t-test and p = 0.03, post-hoc test). On neuropsychological testing, moderate and severe cognitive impairment was revealed in 58.3% of patients with AE and 41.6% of patients with TLE. Hippocampal myo-inositol (M-Ins) concentrations were higher in patients compared to control subjects, with a trend toward increase in AE and TLE relative to control (p = 0.046, ANOVA; p = 0.09 and p = 0.07 for AE and TLE vs. control, respectively; post-hoc tests). The concentration of creatine (tCr) and total choline (tCho) were significantly higher in patients with TLE compared to the controls (tCr: p = 0.007; tCh: p = 0.04; post-hoc tests). Elevated M-Ins in AE was associated with better attention but worse memory recognition scores (R2 = 0.38, p = 0.04 and R2 = 0.50, p = 0.02, respectively); higher tCr levels correlated with faster processing speed (R2 = 0.38; p = 0.04). The higher concentrations of tCr, tCho, and M-Ins in TLE have selectively correlated with worse measures of attention, processing speed, language, and memory.ConclusionsAlthough AE and TLE patients report similar cognitive issues, their hippocampal metabolic signatures differ. The disease-specific changes in the measures of hippocampal inflammation and neuronal integrity can inform trajectories for cognitive recovery and be targeted therapeutically.